Self‐passivation of molecular n‐type doping during air exposure using a highly efficient air‐instable dopant. Issue 10 (23rd July 2013) - Tietze, Max L.; Wölzl, Florian; Menke, Torben; Fischer, Axel; Riede, Moritz; Leo, Karl; Lüssem, Björn
<x xml:space="preserve">Abstract</x> In contrast to p‐dopants, highly efficient molecular n‐dopants are prone to degradation in air due to their low ionization potentials, limiting the processing conditions of doped functional organic devices. In this contribution, we investigate the air‐stability of pure films of the n‐dopant tetrakis(1, 3, 4, 6, 7, 8‐hexahydro‐2H‐pyrimido[1, 2‐a]pyrimidinato)ditungsten(II) (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3ss5m764" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />W2(hpp)4</alternatives>) and of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3ss5m77p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />C60</alternatives> layers doped by <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3ss5m72x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />W2(hpp)4</alternatives>. We find that 1/3 of the initial conductivity of the doped C60 thin films can be restored by thermal annealing in vacuum after a drop by 5 orders of magnitude upon air exposure. Furthermore, we show by ultraviolet photoelectron spectroscopy (UPS) and Seebeck measurements that the Fermi level shift toward the lowest unoccupied molecular orbital (LUMO) of C60 remains after air exposure, clearly indicating a conservation of n‐doping. We explain these findings by a down‐shift of the W2(hpp)4 energy levels upon charge‐transfer to a host material with deeper lying energy‐levels, facilitating a protection against oxidation in air. Consequently, the observed recovery of the conductivity can be understood in terms of a self‐passivation of the molecular n‐doping. Hence, an application of highly efficient n‐doped thin films in functional organic devices handled even under ambient conditions during fabrication is feasible.